2018
DOI: 10.1002/etep.2616
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of grid interfaced photovoltaic system with active power filter capabilities

Abstract: Summary This paper deals with a sixth‐order generalized integrator for single phase grid interlinked solar photovoltaic generation system (PVGS). The objective of the proposed algorithm is to control the power transfer between the photovoltaic (PV) and grid and the load at unity power factor and load current harmonics compensation. The proposed PVGS works in 3 modes: (1) PV‐voltage source converter (VSC), (2) VSC as an active power filter (ie, solar power is zero), and (3) PV‐VSC without the load. The VSC is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…A second order GI is reported in another research for distortion rejection; however, they have been found ineffective in dealing with dominant lower order harmonics and DC offset. A sixth‐order GI composed of three second‐order generalized integrator (SOGI) cascaded in series is presented in another work . The presented structure removes the DC offset.…”
Section: Introductionmentioning
confidence: 99%
“…A second order GI is reported in another research for distortion rejection; however, they have been found ineffective in dealing with dominant lower order harmonics and DC offset. A sixth‐order GI composed of three second‐order generalized integrator (SOGI) cascaded in series is presented in another work . The presented structure removes the DC offset.…”
Section: Introductionmentioning
confidence: 99%
“…These oscillations and variations affect the injected inverter current into the grid and their reference current generation during transients. 3 DC-link reference voltage in a single-stage grid-tied PV system is floating in nature, which is controlled through different maximum power point tracking (MPPT) techniques. 4 However, these techniques have not considered the effects of abrupt irradiation change on the reference DC-link voltage, and hence, the dynamics of the system becomes very poor.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, active power filter (APF) is introduced to overcome these problems. Among different types of APF, shunt APF (SAPF) has been widely applicable as a viable solution …”
Section: Introductionmentioning
confidence: 99%
“…Solar PV power generation has been widely used to meet the energy demand which improves the reliability and power quality while reducing the burden on the central grid. Recently, power quality issues in the grid‐tied system have been addressed by the use of more advanced APF technology . However, SAPF is the most dominant solution to mitigate the power quality problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation